Photo‐Crosslinking Strategy Constructs Adhesive, Superabsorbent, and Tough PVA‐Based Hydrogel through Controlling the Balance of Cohesion and Adhesion. Issue 1 (12th December 2019) - Li, Zhangkang; Wang, Dawei; Bai, Huiyu; Zhang, Shengwen; Ma, Piming; Dong, Weifu
Abstract: An ideal hydrogel with excellent adhesive performance has drawn much attention in research and applications. In this paper, a photo‐crosslinked polyvinyl alcohol bearing styrylpyridinium group/cellulose nanocrystals (PVA‐SbQ/CNC) composite hydrogel is designed through photo‐crosslinking technology for preventing the physical crosslinking of polyvinyl alcohol to maintain enough hydroxy groups in the hydrogel. Thus, the hydrogel exhibits excellent adhesive behavior not only for various solid substrates (plastics, rubbers, glasses, metals, and woods) but also muscle and fat. In addition, the formation mechanism, the swelling behavior, and mechanical strength are also investigated. Also, these results show that photo‐crosslinked PVA‐SbQ/CNC hydrogel possesses high swelling rate, super stretchability, and high toughness. Moreover, adhesive, mechanical, and swelling properties of PVA‐SbQ/CNC hydrogels can be changed with the increase of total incident light intensity. It is anticipated that the photo‐crosslinked PVA‐SbQ/CNC hydrogel would play a significant role in the applications of wound dressing, medical electrodes, tissue adhesives, portable equipment, and super absorbent materials. In this sense, the simple photo‐crosslinking strategy would provide new ideas for designing soft and adhesive materials through controlling the balance of cohesion and adhesion. Abstract : A multifunctional polyvinyl alcohol based hydrogel is designed through photo‐crosslinking technology. The hydrogel possesses strong adhesion, high swelling rate and high toughness. Furthermore, all these properties can be adjusted by changing the exposure time under UV light. It is anticipated that the simple photo‐crosslinking strategy will provide new ideas to design soft and adhesive materials.